Evaluation of Industrial by-products as pozzolans: A road map for use in concrete production. (December 2020) - Bumanis, Girts; Vitola, Laura; Stipniece, Liga; Locs, Janis; Korjakins, Aleksandrs; Bajare, Diana
Highlights: Industrial by-products were compared to commercial pozzolans. Complex evaluations with nine different test methods were performed. A roadmap with criteria and limits for pozzolanic materials is introduced. Abstract: The concrete industry is eagerly pursuing the economic advantages of concrete and the improvement of its long-term properties. One of the most effective approaches to improve concrete properties is associated with replacing part of the Portland cement with pozzolanic additives. Although commercial pozzolans like silica fume have proven to be effective, they come at a high cost. Therefore, the modern construction industry is researching pozzolan alternatives. These new pozzolans could come as by-products from different industries, usually accompanied by low-prices, but their efficiency is questionable in most cases. Therefore, fast and reliable evaluation of the materials' efficiency is necessary. This study aims to summarize techniques adapted for evaluation of pozzolanic materials in a roadmap and do evaluation of waste stream pozzolanic materials. Four characterization directions were considered – chemical and physical analysis (i and ii) and direct and indirect pozzolanic activity test methods (iii and iv). Five commercial or waste stream pozzolanic materials were compared and results evaluated. Industrial by-products (glass E, glass K, metakaolin) are studied as alternative pozzolans and compared to silica fume and fly ash. Selected materials are evaluated using testing methods, such as XRF, FTIR, XRD, micro-granulometry, BET, Frattini test, saturated lime test, strength activity index and alkali–silica reaction tests. The evaluation roadmap for pozzolan quality assessment is proposed. Results indicate that commercial material silica fume can meet the requirements followed by the test procedures given in roadmap. Promising result was obtained for E glass which also passed the quality assessment and showed respectable performance results. Rest of materials failed such an important parameter as alkali content. Besides, it was concluded that only complex dissemination provides a trusted result, as the Frattini test and saturated lime test showed promising results, the results do not always match the results of the strength activity index and alkali–silica reaction.